Interpretation of the plant in the Kazakh and Turkish onomastics (Eurasian Journal of Philology Science and Education, 2020)
In the history of mankind, a special place is occupied by the names of people. Generations of transmission of a significant name are ancient, folk traditions that have remained to us from our ancestors. Names also live, become obsolete and updated, like words in a folk language. And they, as a chronicler of centuries, are passed on to future generations. The first duty of parents to a child is to give a worthy name. Prophet: “On the day of judgment you will be invited by your name and the name of your fathers. Therefore, give your children a good name.”In this article we will consider the linguoculturological semantic features of the names of girls named after flowers, plants in the Kazakh and Turkish languages. Personal names, as well as toponyms, have an important place in the history of Turkish and Kazakh culture. Although there were certain periods when Turkish and Kazakh personal names reflected the strong influence of accepted religions and foreign cultures, the facts show that, in general, the traditional practice of naming was preserved among the Turks and Kazakhs during a long historical process. Basically, studies, comparisons and a comprehensive analysis of anthroponyms in the Kazakh and Turkish languages have not been carried out, they still require research work. Studies of Turkic and Kazakh anthroponymy are necessary not only to determine the specificity and similarity of different languages, but also necessary to understand the features of their worldview and view, national psychology, history, culture of the peoples who use the studied language.